PEMBUATAN PAPAN MOTIVASI HARIAN UNTUK MENINGKATKAN SEMANGAT BELAJAR - Yurike Cono; Nuraliyah Faradillah (Journal of Community Services on Multidisciplinary Sciences, 2025)
The learning process in schools is the main core of the education system, where motivation plays an important role in shaping students' attitudes and behavior. This community service activity focuses on increasing students' learning motivation through the creation of motivational boards as an effective participatory media. The subjects of the activity are elementary school students, with the aim of building awareness of the importance of motivation in academic achievement. The implementation strategy is carried out in a participatory manner, where students write motivational words and their personal goals on the boards provided. This motivational board media not only provides visual stimulation, but also involves students as creators of motivation for themselves. This method encourages active student involvement and creates a more reflective and collaborative learning atmosphere. The results of the activity show that the motivational board creation project contributed to increasing students' enthusiasm for learning and involvement in the learning process, as well as creating a positive learning environment that supports the achievement of optimal learning outcomes.